2006
DOI: 10.1097/01.ajp.0000210924.56654.03
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient-controlled Epidural Analgesia Requirements

Abstract: Our study demonstrated the association between patients' characteristics and total PCEA requirements from a large-scaled clinical data. Surgical procedures have more influence on PCEA consumption than demographic variables. Background infusion rate of PCEA could be determined from our predictive model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…PCEA requirements are determined by the site of surgery, surgery for malignant disease, and also patient weight and age. 92 The addition of a continuous infusion to PCEA during labour resulted in reduced total dose of local anaesthetic while providing effective analgesia. 93 A reduction in local anaesthetic dose was found only in demand-only PCEA, but not with background infusion by Vallejo and colleagues, 94 despite similar outcomes.…”
Section: Bolus Vs Continuous Dosingmentioning
confidence: 99%
“…PCEA requirements are determined by the site of surgery, surgery for malignant disease, and also patient weight and age. 92 The addition of a continuous infusion to PCEA during labour resulted in reduced total dose of local anaesthetic while providing effective analgesia. 93 A reduction in local anaesthetic dose was found only in demand-only PCEA, but not with background infusion by Vallejo and colleagues, 94 despite similar outcomes.…”
Section: Bolus Vs Continuous Dosingmentioning
confidence: 99%
“…10,52 Like IV PCA, epidural analgesia is associated with high patient satisfaction. 50 Single epidural bolus doses of conventional preservative-free morphine are capable of producing pain relief lasting as long as 24 hours and have been used for many years in orthopaedic patients. 10 A novel, extended-release formulation of preservative-free morphine (DepoDur; Endo Pharmaceuticals, Chadds Ford, PA), which consists of multiple microscopic, liposomal (fat-based) particles that encapsulate the morphine, is also administered via a single epidural bolus.…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…53 Both continuous epidural infusions and PCEA are appropriate for the management of major postoperative orthopaedic pain, such as total knee arthroplasty. 2,10,50,51 Although demandonly PCEA therapy is used, the addition of a continuous infusion to the demand feature is most common 50 and provides more continuous pain relief. 10 …”
Section: Epidural Analgesiamentioning
confidence: 99%
“…Chia et al demonstrated negative relation of sex to analgesia [47]. On the other hand, three studies didn't observe significant correlation between sex and postoperative pain [48][49][50] and one study didn't found relation between sex and need for analgesia [51]. H.Y.V.…”
Section: Discussionmentioning
confidence: 99%